Global health and social media: using Instagram and Twitter in an open online class for global service-learning projects. Issue 4 (1st October 2016) - Messner, Marcus; Medina-Messner, Vivian; Guidry, Jeanine
Abstract : Course description: An undergraduate open online course used Facebook, Twitter, and Instagram to explore global health issues and designed social media campaigns for nonprofit clients. Social media platforms were used as teaching as well as learning platforms to allow students to explore their real life applications in global health contexts.